Plasticity, Permanence, and Patient Performance: Study Design and Data Analysis in the Cognitive Rehabilitation of Acquired Communication Impairments - Cowell, Patricia E.; Whiteside, Sandra P.; Windsor, Fay; Varley, Rosemary A. (Frontiers in Human Neuroscience, 2010)
Communication impairments such as aphasia and apraxia can follow brain injury and result in limitation of an individual's participation in social interactions, and capacity to convey needs and desires. Our research group developed a computerised treatment programme which is based on neuroscientific principles of speech production (Varley and Whiteside, 2001; Varley, 2010; Whiteside and Varley, 1998) and has been shown to improve communication in people with apraxia and aphasia (Dyson et al., 2009; Varley et al., 2009). Investigations of treatment efficacy have presented challenges in study design, effect measurement and statistical analysis which are likely to be shared by other researchers in the wider field of cognitive neurorehabilitation evaluation. Several key factors define neurocognitively based therapies, and differentiate them and their evaluation from other forms of medical intervention. These include: (1) inability to “blind” patients to the content of the treatment and control procedures; (2) neurocognitive changes that are more permanent than pharmacological treatments on which many medical study designs are based; and (3) the semi-permanence of therapeutic effects means that new baselines are set throughout the course of a given treatment study, against which comparative interventions or long term retention effects must be measured. This article examines key issues in study design, effect measurement and data analysis in relation to the rehabilitation of patients undergoing treatment for apraxia of speech. Results from our research support a case for the use of multiperiod, multiphase cross-over design with specific computational adjustments and statistical considerations. The paper provides researchers in the field with a methodologically feasible and statistically viable alternative to other designs used in rehabilitation sciences.